Button Operated Gear Shifting System for Two-Wheeler - Sabarish, R.; Jeya Kumar, M. Prem (International Journal of Psychosocial Rehabilitation, 2019)
There is disclosed an automatic gear change control apparatus for an automobile and a method of controlling such apparatus. A rotational output of an internal combustion engine is connected to the drive wheels of the automobile and a load device. When a gear shifting-up of an automatic transmission is to be effected, the load applied by the load device is increased, or the load is connected to an output rotation shaft of the engine via a selectively connecting device, thereby reducing the rotational speed of the output rotation shaft of the engine to a required level. In this project, the push button is used to activate/deactivate the solenoid valve. The switch is ‘ON’ at the time of gear changing; the solenoid valve is activated, so that the compressed air goes to the pneumatic cylinder. There is disclosed an automatic gear change control apparatus for an automobile and a method of controlling such apparatus. A rotational output of an internal combustion engine is connected to the drive wheels of the automobile and a load device. Then the compressed air passes through the tube and then pushes the pneumatic cylinder so that the gear is changed from one speed to another speed with the help of a gearbox arrangement. There is disclosed an automatic gear change control apparatus for an automobile and a method of controlling such apparatus. A rotational output of an internal combustion engine is connected to the drive wheels of the automobile and a load device. When a gear shift-up of an automatic transmission. The load applied by the load device is increased, or the load is connected to an output rotation shaft of the engine via a selectively connecting device, thereby reducing the rotational speed of the output rotation shaft of the engine to a required level. There is disclosed an automatic gear change control apparatus for an automobile and a method of controlling such apparatus. A rotational output of an internal combustion engine is connected to the drive wheels of the automobile and a load device. When a gear shifting-up of an automatic transmission is to be effected, the load applied by the load device is increased, or the load is connected to an output rotation shaft of the engine via a selectively connecting device, thereby reducing the rotational speed of the output rotation shaft of the engine to a required level. In this project, the push button is used to activate/deactivate the solenoid valve. The switch is ‘ON’ at the time of gear changing; the solenoid valve is activated, so that the compressed air goes to the pneumatic cylinder. Then the compressed air passes through the tube and then pushes the pneumatic cylinder so that the gear is changed from one speed to another speed with the help of a gearbox arrangement.